Development of E-Modules Based on Discovery Learning on Temperature and Heat Material to Improve Communication Skills of Grade V Elementary School Students - Wijayanti, Eka; Suparti, Suparti; Wahyuni, Sri (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this study was to describe the results of the validity, practicality, and effectiveness of the development of Discovery Learning-Based E-Module Media to Improve Communication Skills of Fifth Grade Elementary School Students. With the development of E-Module science learning based on Discover Learning, it is expected to motivate students in the learning process and can increase student activity in learning Theme 6 Subtheme 1 Temperature and Heat. The research design used is Research and Development (R&D) development research. The development model in this study uses the ADDIE model. The research instruments used are expert validation questionnaires, teacher and student response questionnaires and learning outcome tests. Based on the research conducted, the results of the level of validity of the learning media obtained from the results of the validation of material experts and learning media experts obtained the Valid criteria. While the results of the practicality test of the media developed based on the results of the teacher and student response questionnaires obtained the criteria of very practical learning media and the results of the practicality test seen from student learning outcomes obtained the criteria of effective media used to improve student learning outcomes. Based on the results of the data analysis carried out, it can be concluded that the developed learning media has been proven to be valid, practical and effective for use to improve the communication skills of fifth grade elementary school students.